Tech-Enabled Flexible Work Aligned with Islamic Values: Enhancing Employee Productivity through Work–Life Balance and the Islamic Work Ethic - Ridwansyah; Sumin; Suhrawardi Suhrawardi; Mohd Shahrul bin Kamaruddin; Khamim Khamim (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2025)
The digital transformation following the COVID-19 pandemic has accelerated the adoption of technology-based flexible working arrangements. In Indonesia’s Islamic public sector, particularly within Islamic Higher Education Institutions, the implementation of flexible working arrangements remains limited due to technological constraints, bureaucratic culture, and challenges in integrating digital HR systems. Research examining the relationship between technology-based flexible working, work-life balance, and employee productivity—along with the moderating role of the Islamic work ethic—remains scarce. This study aims to investigate the effect of technology-based flexible working on employee productivity, with work-life balance as a mediating variable and the Islamic work ethic as a moderating variable. Employing a causal-correlational design and survey methodology, the study sampled 440 lecturers and educational staff from Islamic Higher Education Institutions in Indonesia, selected through simple random sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 4.1.1.4. The results indicate that technology-based flexible work arrangements increase employee productivity but negatively impact work-life balance. Work-life balance serves as a crucial mediator bridging the relationship between flexibility and productivity. Additionally, the Islamic work ethic plays a dual role: it directly predicts work-life balance and moderates the relationship between work flexibility and balance, strengthening this association. The findings imply that organizations must do more than merely adopt technology; they must also safeguard work-life balance and internalize the Islamic work ethic to achieve sustainable productivity. Limitations of this study include its cross-sectional design and focus on the Islamic cultural context, suggesting that generalization to other sectors requires longitudinal and cross-cultural research.